Introduction Lessons Learned from Data Mining Applications and Collaborative Problem Solving. - Lavrac, Nada (Machine learning.)
This introductory paper to the special issue on Data Mining Lessons Learned presents lessons from data mining applications, including experience from science, business, and knowledge management in a collaborative data mining setting.